A unified theory of the firm from tawhidic worldview: the views of mu’amalat management and economics scholars - Mhd. Sarif, Suhaimi; Ismail, Yusof; Abdul Sabian, Nur Arfifah (2013)
The theory of the firm subscribes to mainstream economic theories that emphasize on profit maximization and cost minimization. Despite its usefulness, the scope of the theory is inadequate to address the contemporary dynamism. A unified theory of the firm bears strong influence of the industrial cost minimization. This study argues a unified theory of the firm from Tawhidic paradigm for a comprehensive theory to describe the nature of the firm, the scope and boundaries of assessment on organizational environments, and the assessment of internal organizations to formulate, implement and evaluate organizational strategies. The conventional approach to the theory of the firm seems inadequate to respond to external and internal environments of the firm, and human dynamism and spiritual identity. The market-based theory of the firm emphasizes primarily on the industrial organizational perspective of the firm. The evolutionary approach of resource-based and knowledge-based theory of the firm is also unable to provide a unified theory of the firm due to lack of spirituality foundation to sustain intellectual contribution from knowledge workers. As an alternative, this study proposes a unified theory of the firm Tawhidic worldview as a mean to achieve organizational sustainable innovation and competitive advantage. The study uses focus group discussion with scholars in management, economics, and Shari’ah studies to provide input on the development of the model of Islamic theory of the firm. The feedback from the experts is used as input to enhance the understanding of Tawhidic worldview in the development of a unified theory of the firm. The results of the study should be considered tentative, or work-in-progress. Future research should incorporate more informants to further debate the dynamics of key components in the subject matter of the study.